Development of Learning Community Based on Sangahavatthu 4 Principles - Vādasaddho, Phraphalad Honda; Marasri, Sarinya; Thanapanyo, Phra Maha Amphon; Mahahing, Prachit (Journal of Buddhist Education and Research (JBER), 2026)
This academic article aims to present a conceptual framework for developing learning communities based on the Four Saṅgahavatthu principles—the Buddhist foundations of social solidarity. The study integrates the Saṅgahavatthu 4, namely Dāna (generosity), Piyavācā (kindly speech), Atthacariyā (beneficial conduct), and Samānattatā (impartiality and consistency), with the concept of the Professional Learning Community (PLC). The findings reveal that the Saṅgahavatthu 4 can effectively drive the development of learning communities: Dāna promotes the sharing of knowledge and resources; Piyavācā fosters constructive communication; Atthacariyā encourages collaborative actions for the common good; and Samānattatā builds trust through fairness, consistency, and equity. Together, these principles contribute to learning communities characterized by cohesion, mutual support, and sustainability.